Reduction and return of infectious trachoma in severely affected communities in Ethiopia. - Takele Lakew; Jenafir House; Kevin C Hong; Elizabeth Yi; Wondu Alemayehu; Muluken Melese; Zhaoxia Zhou; Kathryn Ray; Stephanie Chin; Emmanuel Romero; Jeremy Keenan; John P Whitcher; et al. (Public Library of Science (PLoS), 2009)
Antibiotics are a major tool in the WHO's trachoma control program. Even a single mass distribution reduces the prevalence of the ocular chlamydia that causes trachoma. Unfortunately, infection returns after a single treatment, at least in severely affected areas. Here, we test whether additional scheduled treatments further reduce infection, and whether infection returns after distributions are discontinued.Sixteen communities in Ethiopia were randomly selected. Ocular chlamydial infection in 1- to 5-year-old children was monitored over four biannual azithromycin distributions and for 24 months after the last treatment.The average prevalence of infection in 1- to 5-year-old children was reduced from 63.5% pre-treatment to 11.5% six months after the first distribution (P<0.0001). It further decreased to 2.6% six months after the fourth and final treatment (P = 0.0004). In the next 18 months, infection returned to 25.2%, a significant increase from six months after the last treatment (P = 0.008), but still far lower than baseline (P<0.0001). Although the prevalence of infection in any particular village fluctuated, the mean prevalence of the 16 villages steadily decreased with each treatment and steadily returned after treatments were discontinued.In some of the most severely affected communities ever studied, we demonstrate that repeated mass oral azithromycin distributions progressively reduce ocular chlamydial infection in a community, as long as these distributions are given frequently enough and at a high enough coverage. However, infection returns into the communities after the last treatment. Sustainable changes or complete local elimination of infection will be necessary.ClinicalTrials.gov NCT00221364.